Implementasi Undang-Undang Nomor 20 Tahun 2011 Tentang Rumah Susun (Studi Pada Rumah Susun Sederhana Sewa Di Kecamatan Sidoarjo Kabupaten Sidoarjo) - Subaktiawan, Eko; Fauziah, Luluk (Universitas Muhammadiyah Sidoarjo, 2017)
This research aims to describe the implementation, the role of actor, and the proponent factors and resistor factors of Law Policy 2011 No. 20 about Flat in Rental Simple Flat of Sidoarjo Subdistrict and Sidoarjo Regency. This research uses qualitative descriptive method. Data accumulation technique is made by abservation, interview and documentation. While the analysing technique started from data accumulation, data reduction, data presentation, and getting the conclusion. The result shows that the implementation of flat development policy hasn’t been running well, socialiszation to the society hasn’t been overall, and the resources to manage flat haven’t been quite enough, but the employees are discipline enough and responsible to do their duties, the bureaucracy structure has been good, the authority distribution has been fair and definite. The actor who has a role is the government as a main implementator, private party as a construction service provider and society as the user. The proponent factors are discipline employees on doing disposition and bureaucracy structure is affirming the duties distribution. While, the resistor factors are the less socialiszation to the society and the minimizing of flat operational resources.